Are victims truly worse off in the presence of bystanders? Revisiting the bystander effect - Hanna Fromell; Daniele Nosenzo; Trudy Owens; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
Previous studies have shown that individuals are less likely to help a person in need when there are "bystanders" present who can also offer help. We designed an experiment to re-examine this "bystander effect" using modified dictator games. We find lower giving rates in the presence of bystanders, confirming the existence of a bystander effect. However, we also show that the recipient's welfare is greater when bystanders are present, challenging the usual interpretation that the bystander effect is due to an erosion of prosocial values.
Keywords: C92; D64; 330; bystander effect; bystander dilemma; diffusion of responsibility; dictator game; socialnorms